Internet access, female’s non-farm employment, and income effects: insights from China - Kunxi Nie; Yueji Zhu (Agricultural and Food Economics)
Abstract Females’ participation in non-farm employment contributes prominently to social progress. Based on the data of 1674 rural females and 1656 urban females in China, this paper evaluates the effects of internet access and four specific online activities (online interaction, online service, online learning, and online entertainment) on females’ non-farm employment using the endogenous switching Probit model. Further, the treatment effect model is employed to explore the role of online work, as a typical non-farm employment based on internet, in increasing household income and in reducing rural–urban income gap. The results show that internet access significantly contributes to females’ non-farm employment and the effect is stronger for rural females than urban females. In terms of online activities, participation in online interaction and online entertainment have positive impacts on rural females’ non-farm employment, while participation in online service, online learning and online entertainment exert positive effects on urban females’ non-farm employment. This study also finds that females’ online work increases household income in both rural and urban areas. The rural–urban income gap is narrowed since rural households’ income has been increased more than urban households. Thus, we propose implications for policy makers to support females in internet access and non-farm employment.